2000
DOI: 10.1136/jms.7.2.91
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying the screening interval on false positives and duration of undiagnosed disease in a screening programme for type 2 diabetes

Abstract: Objectives-The aims of this study were to quantify the proportion of people diagnosed as having type 2 diabetes by standard 75 g oral glucose tolerance test, in a hypothetical screening programme, who would actually be false positives (false positive percentage), and the eVect on the false positive percentage of varying the time between repeat screens. We also calculated the duration in person years of exposure to undiagnosed disease in the population for each screening interval. Setting-Ely, Cambridgeshire, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…This result is in contrast to a number of studies, which show relatively low repeatability in terms of re-classifying NGT, IGT and T2DM subjects (50-65% repetition) [7,10,34]. In contrast, Fig.…”
Section: Comparison To Other Testscontrasting
confidence: 90%
“…This result is in contrast to a number of studies, which show relatively low repeatability in terms of re-classifying NGT, IGT and T2DM subjects (50-65% repetition) [7,10,34]. In contrast, Fig.…”
Section: Comparison To Other Testscontrasting
confidence: 90%
“…By definition, it needs at least two separate measures of glycaemic disturbance on separate days before the clinical diagnosis of CFRD can be made in this group of patients mainly displaying no acute symptoms of diabetes [10,13]. In a non-CF population screened by OGTT for type-2 diabetes 1 yr after the initial diabetic OGTT, a second OGTT returned to nondiabetic in 47% of the subjects [14]. In a CF population with an annual OGTT screening programme, only 10 out of 15 patients who were diabetic in the annual OGTT were also diabetic in a repeated OGTT [15].…”
Section: Discussionmentioning
confidence: 99%
“…(Ferrannini et al 2005) found a R=0.74 correlation between the 2-hour oral-glucose tolerance test (OGTT) and the clamp which is comparable to our in silico correlation of R=0.81. However, the reproducibility of the OGTT has been called into question by a number of researchers who found NGT, IGT and T2DM re-classification rates of only 50-65% (Ko et al 1998;Levy et al 1999;Park et al 2000).…”
Section: Resultsmentioning
confidence: 99%